Hymns to Meslamtaea, Lugalgirra and Nanna-Suen in Honour of King Ibbīsuen (Ibbīsîn) of Ur - Sjöberg, Åke W. (1970)
ersch. 1972; 172-178: photos CBS 11168, CBS 14053, UM 29-16-43, CBS 8526, UM 29-13-609, CBS 15158.